Comparison of Thermal Properties of PCB Photoresist Films Cured by Different Techniques - Piyachat Wattanachai; Christian Antonio; Susan Roces (ASEAN Journal of Chemical Engineering, 2016)
The possibility of implementing microwave technology to photoresist film curing which is a major process in the production of electronic printed circuit boards (PCB) was investigated and compared with a conventional curing method, e.g. UV lithography. Since both techniques involved irradiation, hot plate curing which relies on thermal conduction was undertaken to study the effect of a heat transfer approach. Two film thicknesses were studied, i.e. 0.0012 and 0.002 inch, and the effects of curing power and time were investigated. Thermal properties, i.e. percent cure, glass transition temperature (Tg), composition and degradation temperature (Td), were evaluated using a Differential Scanning Calorimeter (DSC) and Thermogravimetric Analysis (TGA) and it was found that the commercial UV irradiation was sufficient to completely cure the thin film but only reached 76% cure for the thicker film, resulting in a lower Tg. The results show that the required processing conditions using a conventional household microwave to obtain almost complete curing were 1,000 Watts and 10 minutes curing time. In addition, improved curing was achieved in the thicker film because microwave can transmit into polar materials whereas UV cannot penetrate very far into the material. The hot plate curing was observed to produce a higher degree of curing and Tg, however, the uniformity of heating was found to be a major limiting factor of this technique. Slight differences in decomposition profiles of the films cured by different techniques implied slight differences in molecular structures. Compared to UV and hot plate curing, microwave technology was demonstrated as a potential curing technique in the production of PCBs due to its ability to efficiently cure thick films resulting in a strong material with high Tg. To apply the technique to other processes, optimal conditions, i.e. power and time, should be further investigated as well as the prevention of hot spots.